2023
DOI: 10.1002/pen.26313
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the mechanical properties and microstructure of the weld joint obtained by laser welding of PA12/CNT nanocomposites

Abstract: In this article, the 3D printed polyamide12/carbon nanotube (PA12/CNT) nanocomposites were joined using laser welding. The factorial design method was applied to study the effect of laser power, welding velocity, and CNT content on the tensile and impact strengths of welded samples. The differential scanning calorimetry and thermogravimetric analysis were also used to measure the thermal stability and weight loss temperature of the nanocomposite. The results indicated that the increase of CNTs enhanced the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The simulation was carried out using the commercial finite element software COMSOL Multiphysics®, which implemented a volume heat source to model the absorption of laser radiation in the transparent‐absorbent substrates. The model proposed in this study for the laser power profile at the interface is based on the classical model presented in previous literature 2,6,13 . In this model, the laser beam power propagated through the transparent component is modeled in terms of a Gaussian beam as described in Equation (1): IX,Y,Z=1Rs×δZ×PO2πσ02expX()t22σ02+Y022σ02. Where P 0 is the initial laser power, σ0 is the initial surface distribution, Rs is the reflection coefficient, and δZ is the light scattering ratio.…”
Section: Numerical Model Used For Inverse Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation was carried out using the commercial finite element software COMSOL Multiphysics®, which implemented a volume heat source to model the absorption of laser radiation in the transparent‐absorbent substrates. The model proposed in this study for the laser power profile at the interface is based on the classical model presented in previous literature 2,6,13 . In this model, the laser beam power propagated through the transparent component is modeled in terms of a Gaussian beam as described in Equation (1): IX,Y,Z=1Rs×δZ×PO2πσ02expX()t22σ02+Y022σ02. Where P 0 is the initial laser power, σ0 is the initial surface distribution, Rs is the reflection coefficient, and δZ is the light scattering ratio.…”
Section: Numerical Model Used For Inverse Methodsmentioning
confidence: 99%
“…To achieve optimal weld quality and the mechanical performances, it is necessary to have a precise prediction of the laser intensity distribution at the weld interface 12 . Samadi et al in reference, 13 have presented the effect of the laser transmission welding (LTW) process parameters on the mechanical strengths of the welded polymer composites components. They have demonstrated that laser power and laser speed have a significant influence on the mechanical strength of the produced assemblies.…”
Section: Introductionmentioning
confidence: 99%